Polarization gating spectroscopy of normal-appearing duodenal mucosa to detect pancreas cancer - Patel, Mihir (Gastrointest Endosc, 2014)
BACKGROUND: According to field effect theory, by detecting microvasculature changes in the early increase of blood supply (EIBS) in the surrounding tissue neoplastic lesions can be identified from a distance. OBJECTIVE: To determine the feasibility and efficacy of a fiberoptic probe containing novel Polarization Gating Spectroscopy (PGS) technology to identify patients with pancreatic adenocarcinoma (PAC) by field effect theory. DESIGN: Prospective cohort (pilot) study SETTING: Outpatient tertiary care center PATIENTS: Adult (≥18 years) patients undergoing EGD-EUS were screened. Patients with PAC were included in the “cancer” group and patients without PAC were included in the “control” group. We excluded patients with other known malignancies and gastro-duodenal premalignant lesions. INTERVENTIONS AND MAIN OUTCOME MEASURES: Spectroscopic measurements of EIBS variables, such as deoxyhemoglobin concentration (DHb) and mean blood vessel radius (BVR), were obtained from five peri-ampullary locations. The Mann-Whitney rank sum test was used for the statistical analysis (p≤0.05). RESULTS: Fourteen patients (mean age: 72 years,79% male) in the cancer group and 15 patients (mean age 63 years,60% male) in the control group were included in the final analysis. At the ampullary site, both DHb (p=0.001) and BVR (p=0.03) were higher in PAC patients than in the controls. The DHb alone (92% sensitivity,86% specificity) or in combination with BVR (92% sensitivity,71% specificity) can differentiate PAC from controls with high accuracy. LIMITATIONS: Small sample size, Unmatched controls CONCLUSIONS: Spectroscopic measurements of EIBS by fiberoptic probes are feasible. Preliminary evidence suggests that in vivo measurement of normal-appearing duodenal tissue can differentiate PAC patients from a distance with high accuracy.